Investment banking in 2008 (A) : rise and fall of the Bear - Stowell, David; Meagher, Evan ([London] : SAGE, 2016)
Gary Parr, deputy chairman of Lazard Freres & Co. and Kellogg class of 1980, could not believe his ears. 'You can't mean that,' he said, reacting to the lowered bid given by Doug Braunstein, JP Morgan head of investment banking, for Parr's client, legendary investment bank Bear Stearns. Less than 18 months after trading at an all-time high of $172.61 a share, Bear now had little choice but to accept Morgan's humiliating $2-per-share, Federal Reserve-sanctioned bailout offer. This case study discusses this topic.
Originally Published in: Stowell, D., & Meagher, E. (2009). Investment Banking in 2008 (A): Rise and Fall of the Bear. 5-308-507(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Bear, Stearns & Co; Investment banking -- Case studies; Financial institutions -- Management -- Case studies; Crisis management -- Case studies; Global Financial Crisis, 2008-2009 -- Case studies